The Effect of Cooking Time on the Organoleptic Characteristics, of Moisture Content, and Fat Content of Smoked Catfish with Coconut Coir Smoking Sources - Fahrul, Fahrul; Syahrul, Syahrul; Usman, Muh. Syawal; Rauf, Jumriah; Abugar, Rizqah (Agrikan Jurnal Agribisnis Perikanan, 2023)
Smoking is one way of preserving fish with the aim of reducing water content and giving a distinctive aroma to the smoked product. This study aims to determine the best length of smoking time for organoleptic value, moisture content, and fat content of smoked catfish. This research was conducted from April to October 2022. Sampling of catfish was carried out in one of the catfish farmers in Tanjung Merdeka Village, Tamalate District, Makassar City, South Sulawesi using purposive sampling method. The research design used was a complete randomized trial design with the treatment of smoking time 3, 4, 5, and 6 hours, each treatment was repeated 3 times. Then the smoked catfish samples were analyzed for organoleptic values at the Faculty of Marine and Fisheries Sciences (FIKP), Hasanuddin University, and the analysis of water content and fat content was carried out at the Integrated Biochemistry Laboratory, Faculty of Animal Husbandry, Hasanuddin University. The results showed that the length of smoking time had a significant effect (p<0.05) on the characteristics of organoleptic values (taste, smell, color and texture), moisture content, and fat content. 5 hours of smoking is the best length of time for organoleptic values from the aspects of taste, smell, color, and texture, where the values are respectively (8.2; 8.2; 8.5; and 7.9), the value of water content is 49.06%, and fat content is 1.43%. Thus, it can be concluded that the best length of smoking time is 5 hours.